(untitled) (Global Journal of Management and Business Research, 2018)
This study focused on Occupational stress and its effect on the job effectiveness of lecturers in federal universities in Akwa Ibom and Cross River states of Nigeria. The Cross sectional survey research design was adopted. The stratified random sample size was 584 lecturers. The research instrument employed in this study was Workload Stress Scale (WSS) and Job Effectiveness Questionnaires (JEQ). The hypothesis was tested using the multiple regression analysis. The analysis results indicated that stress from factors – workload, facilities, career development requirements and organizational climate significantly joint predict job effectiveness of lecturers while inter personal relationships and funding were not significant predictors. It was recommended that universities should reduce the workload of lecturers by adhering to the National University Commission’s studentlecturer ratio. Also adequate infrastructural facilities should be provided.